EFFECTIVENESS OF THE LEVEL OF SERUM CALCIUM IN HYPO- AND HYPERTHYROIDISM PATIENTS AT TERTIARY CARE HOSPITAL, KANPUR - Yadav, Satish Kumar; SINGH, SATYAPRAKASH; CHAUDHARY, RAJMANGAL (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Hypothyroidism and hyperthyroidism are two primary pathological conditions that involve thyroid glands. Thyroid dysfunction amends calcium metabolism thereby necessitating regular monitoring of calcium levels The aim of the study is to find the prevalence of the level of serum calcium in hypo- and hyperthyroidism patients at tertiary care hospital Kanpur Methods: The Department of Biochemistry carried out this research at RMCH and RC, Kanpur, for 1 year between February 2019 and January 2020. In our study, we have taken 150 patients and classified them into three groups. Each group belonging to 50 subjects in total 100 subjects were suffering from thyroid. The left 50 subjects were normal and used as control for making a better understanding of hyper- and hypothyroidism. After study there thyroid profile and calcium level from the standard method. 5 mL of fasting venous blood sample was collected from each patient. In the present study, following analyses were conducted, thyroid function test (T3, T4, and thyroid-stimulating hormone [TSH]) and serum calcium. Result: Out of 150 samples, in the present investigation, we find that the mean age group was 20–30-year-old patients included. Which number was higher in the group 1st (hyperthyroidism.) and 2nd group patients belonging 20–30 years but our value also indicated the same number in the age group 41–50-year hypothyroidism, whereas in the control group, we took that maximum age group was 20–30 years old, while investigated hyperthyroid patients, we observed mean value of T3=1.23±0.67, T4=8.15±2.43, TSH=0.16±0.13, and calcium 11.94±0.53. During the investigation of hypothyroidism patients, we find the following values of T3=0.87±0.27, T4=7.53±2.05, TSH=50.93±55.77, and Ca=7.53±0.75. Conclusion: In our study, we found that serum calcium is affected by the thyroid hormones. Whenever there are any thyroid hormone disturbances, alterations in the levels of serum calcium should be looked for to prevent any abnormalities from occurring.